Предмет: Алгебра,
автор: яяяя561
выполните действия: х^3+2 дробь 1-х^3 + 3 дробь х^3-1
Ответы
Автор ответа:
0
-1
Автор ответа:
0
-1 ответ
Автор ответа:
0
(x^3+2)/(1-x^3))-(3/(1-x^3)=
=(x^3+2-3)/(1-x^3)=
=(x^3-1)/(1-x^3)=(-(1-x^3)/
/(1-x^3)= -1
=(x^3+2-3)/(1-x^3)=
=(x^3-1)/(1-x^3)=(-(1-x^3)/
/(1-x^3)= -1
Похожие вопросы
Предмет: Алгебра,
автор: kristinasaapina938
Предмет: Математика,
автор: kanim4392
Предмет: Русский язык,
автор: Аноним
Предмет: Геометрия,
автор: elias4mi
Предмет: Математика,
автор: pingwinovedik